2015
DOI: 10.1016/j.echu.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Approaches to Diagnostic Imaging Education: A Narrative Review of the Literature

Abstract: ObjectiveThe purpose of this study was to examine literature on how radiology is taught and learned by both radiology residents and undergraduates in the health professions.MethodsA review of the literature was performed using relevant key words. Articles were retrieved through December 2012 using PubMed, ScienceDirect, ERIC, Proquest, and ICL databases along with a manual review of references.ResultsOf the 4716 unique abstracts reviewed by the author, 91 were found to be relevant to the purpose of this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Although previous literature has revealed that a mainstay of radiology education was self-learning, the technology could not replace the dedication of human educators. [ 12 ] Similar results have been demonstrated by Cawthorn et al . [ 7 ] They compared US image acquisition quality between the simulator-trained group and sonographer-trained group and found that mean quality scores of the simulator-trained group were significantly lower than those of sonographer- trained group.…”
Section: Discussionsupporting
confidence: 87%
“…Although previous literature has revealed that a mainstay of radiology education was self-learning, the technology could not replace the dedication of human educators. [ 12 ] Similar results have been demonstrated by Cawthorn et al . [ 7 ] They compared US image acquisition quality between the simulator-trained group and sonographer-trained group and found that mean quality scores of the simulator-trained group were significantly lower than those of sonographer- trained group.…”
Section: Discussionsupporting
confidence: 87%
“…However, there is very little research in the radiology trainee's education literature exploring these areas that allow a better evaluation of one of the many aspects present in academic formation, allocation of resources and training of residents in diagnostic area serving as backbone any medical center. To our knowledge, no such study has ever been done to understand how radiology is taught, learned and perceived by radiology residents and its relation to the overall environment 4…”
Section: Introductionmentioning
confidence: 99%
“…In image interpretation education, recent shifts away from the container model as the dominant instructional approach have occurred in radiology education [4]. Radiograph interpretation represents a complex skill since learners must apply their knowledge of anatomy and pathology and their problem-solving skills to assess each image and reach a diagnosis or conclusion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Radiograph interpretation represents a complex skill since learners must apply their knowledge of anatomy and pathology and their problem-solving skills to assess each image and reach a diagnosis or conclusion [5]. In addition to absorbing relevant declarative knowledge, learners must restructure and adapt their knowledge for each new image [4]. In radiology education, traditional teaching methods have been gradually replaced by more interactive approaches, such as case-based instruction [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation